A STUDY OF INDONESIAN MILLENIAL STUDENTS’ LEARNING STYLES IN ENGLISH LANGUAGE LEARNING - Putri Nurtasha; Ghyarlina Triyani (UICELL, 2021)
Learning style is one of the important aspects for both students and teachers so that learning objectives achieved. Students have their own characteristics and strategies that distinguish them from one another. Student learning styles focus on personality learning or problem solving in the classroom. Therefore, the aim of this research is to analyze the students learning styles who Indonesian millennial students use in English language learning. The subjects of this research is the second semester students at Universitas A Pontianak. The population of this research is six students that will take randomly. The research employs a qualitative descriptive method as the research design. The researcher will apply the questionnaire to collect the data. The questionnaire will adopted from the VARK Learning Styles Questionnaire version 8.01, it provides 16 questions item with four optional answers (A,B,C,D). The expected result is to provide useful information for all readers about learning styles especially in English language learning and also get better understanding about the best way of learning. Keywords: Millennial, Language Learning VARK, Learning Styles